Volume 5: Materials Technology; CFD and VIV 2008
DOI: 10.1115/omae2008-57344
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Investigation of Vortex Induced Vibration on an Elastically Mounted Rigid Cylinder

Abstract: The Vortex-Induced Vibration on an elastically mounted circular cylinder is investigated by the numerical solution of the two-dimensional Reynolds Averaged Navier-Stokes equations and results are compared with experimental data. The upwind TVD scheme of Roe – Sweby is used to solve the governing equations and the k-ε turbulence model is used to simulate the turbulent flow in the wake of the cylinder. The cylinder is laterally supported by a spring and a damper and is free to oscillate in the transverse directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Previous calculations by Wanderley et al (2008b) have already proved that an O-grid around a vibrating circular cylinder with 200 Â 200 nodes, using stretching parameter q η ¼ 1.020 in the radial direction, and body surface to external boundary distance of 120 diameters is adequate for the numerical modeling of the flow. For details about the grid effect test, refer to Wanderley et al (2008b).…”
Section: Grid Generationmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous calculations by Wanderley et al (2008b) have already proved that an O-grid around a vibrating circular cylinder with 200 Â 200 nodes, using stretching parameter q η ¼ 1.020 in the radial direction, and body surface to external boundary distance of 120 diameters is adequate for the numerical modeling of the flow. For details about the grid effect test, refer to Wanderley et al (2008b).…”
Section: Grid Generationmentioning
confidence: 98%
“…In Wanderley et al (2008b), the numerical code was validated for VIV simulations by duplicating in accurate and reliable way the benchmarking experimental results obtained by Khalak and Williamson (1996). The same experimental setup was considered throughout the numerical simulation and also the same mass ratio of C μ ¼1.88, damping ratio of ξ¼5.42 Â 10 À 3 , and reduced velocity varying from 2 to 12, corresponding to Reynolds number variation from 2000 to 12,000.…”
Section: Numerical Code Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (1) is solved numerically together with the initial conditions (8), boundary conditions on the body surface (9), and freestream boundary conditions (10), where I is the turbulence intensity, _ y is the velocity of the cylinder in the y direction, and M 1 ¼ 0.2 for incompressible flows.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The 2S mode is associated with high amplitudes and is responsible for the high amplitudes found in the displacement amplitude curve. In Wanderley et al [8], the numerical results indicated that the transition from the 2S mode to the 2P mode of vortex shedding takes place exactly when the curve of power absorbed by the system changes declivity. For rising power absorption, the 2S mode is observed, and for falling power absorption, the 2P mode governs the vortex shedding.…”
Section: Introductionmentioning
confidence: 95%